YOU'RE A STAR, LOLO - Daly, Niki (Hereford : Otter-Barry Books, 2020)
Third in the Lolo series: four new adventures of the sparky young South African heroine who lives with her Mama and Granny Gogo. Lolo hears strange sounds at night; starts a garden at school and has to choose between tomatoes and snails; goes with Gogo for a lovely holiday by the sea but they have a problem about how to get home ... these are everyday happenings told in simple language with zest and humour. Lolo is someone every child can empathise with, and at the same time get to understand a way of life very like their own but with some interesting differences.
Lolo's special soup -- Lolo's scary night -- Lolo's snail garden -- Lolo's holiday.
6-9 years.
Keywords: Lolo, -- (Fictitious character from Daly) -- Juvenile fiction; Girls -- South Africa -- Juvenile fiction; Families -- Juvenile fiction; Winds -- Juvenile fiction; Snails -- Juvenile fiction; Children's stories; Humorous fiction